Pengaruh Brand Image, Kualitas Layanan Internet Banking, dan Tingkat Kepuasan Terhadap Loyalitas Pengguna (Studi Kasus Pada PT. Bank Rakyat Indonesia (Persero) Tbk., Kantor Cabang Khusus) (Ekonomika, 2022)
This study examines the influence of Brand image, service quality, and rate of satisfaction on customer loyalthy (for example, customer PT Bank Rakyat Indonesia-Persero). The independent variables in this study are Brand Image, Service Quality, and Rate of Satisfaction. This is the customer loyalthy made by a PT. Bank Rakyat Indonesia (Persero). The data collection method is used by sending questionnaires. The analysis method used in this study are based on the data of 100 customers of PT. Bank Rakyat Indonesia, using the coefficient of determination analysis, multiple regression analysis F-test and SPSS 26.00 testversion. It can be seen from the t-test results that the brand image t-value is 2.080, the service quality t-value is 8.052, and the rate of satisfaction t-value is 3.255, which are all greater than the t intable 1.688. This indicates that the brand image, the service quality and the rate of satisfaction may have a positive impact on the customer loyalthy of PT. Bank Rakyat Indonesia. F-count>F-table or 31.004>2.87or significance level (signal) 0.000. The adjusted definition shows that the influence of brand image, the service quality, and the rate of satisfaction are 69.8%.In this study, the adjusted R2 value is 69.8%, which means that the dependent variable of PT Bank Rakyat Indonesia’s customers maybe different. We canuse 69.8% of the model to explain using explanatory variables, and there maining 30.2% isused for other variables besides independent variables, namely the contribution of the brand image, the service quality, and the rate of satisfaction. the remaining 30.2%, namely the level of other variables that are not related to Brand Image, Service Quality, and Satisfaction Level.